2019
DOI: 10.1155/2019/3170957
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ticagrelor versus Clopidogrel in Patients with Coronary Bifurcation Lesions Undergoing Percutaneous Coronary Intervention

Abstract: Background. Percutaneous treatment of coronary bifurcation lesions can potentially lead to higher risk of ischemic events than the nonbifurcation ones, thus calling for further optimization of dual antiplatelet therapy (DAPT). This study aimed to compare the clinical outcomes from ticagrelor and clopidogrel in bifurcation lesions patients undergoing percutaneous coronary intervention (PCI). Methods. We performed a retrospective cohort study in patients with coronary bifurcation lesions. A total of 553 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…In our study, clopidogel was given to 24% of patients and found to be another important predictor of the presence of MACE. In harmony with our finding, Zheng et al found that for patients with bifurcation stenting, ticagrelor was superior to clopidogrel in terms of MACE and MI rates [32].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, clopidogel was given to 24% of patients and found to be another important predictor of the presence of MACE. In harmony with our finding, Zheng et al found that for patients with bifurcation stenting, ticagrelor was superior to clopidogrel in terms of MACE and MI rates [32].…”
Section: Discussionsupporting
confidence: 92%
“…PASS software version 11.0 was used to calculate power and determined the sample size based on previous studies and our estimates [18,19]. Calculation formula for sample size as follow: see formula 1 in the supplementary les.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, diabetic patients were selected because they are a well-established subgroup of patients with ED, independently by cardiologic clinical presentation [7]. The choice to investigate the effects of ticagrelor on ED is in apparent contrast with a study showing that the anti-aggregatory effects of ticagrelor are less pronounced during acute inflammation [59], but is supported by data showing pleiotropic effects of ticagrelor beyond its potent antiplatelet effects [60,61]. Consistently, we found reduced levels of surrogate markers of endothelial dysfunction in patients with stable CAD and concomitant COPD following PCI and 1-month treatment with ticagrelor, but not with clopidogrel [6].…”
Section: Discussionmentioning
confidence: 99%